2007
DOI: 10.3323/jcorr.56.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparative XPS Study of Silver and Copper Surfaces Exposed to Flowing Air Containing Low Concentration of Sulfur Dioxide

Abstract: Sulfur dioxide (SO 2 ), a typical gaseous compound found in the atmosphere, corrodes metals, particularly outdoors. When SO 2 adsorbs on the surface electrolyte, it easily dissolves, resulting in the formation of protons (H ) and bisulfite ions (HSO 3 ). The former reduces the pH of the surface electrolyte, which promotes metal dissolution.Silver and copper are commonly used in the electronic components and devices typically found in telecommunication equipment. Since silver and copper are affected by SO 2 , i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…3(d)), peaks at 168.3 and 169.7 eV for fresh IL/Al 2 O 3 are corresponding to S 2p 3/2 and S 2p 1/2 of -SO 4 , respectively. 64,65 The binding energy in Pd-x%IL (x = 2, 4, 6) shifts to 168.8 and 170.2 eV, respectively, which also results in a decrease in electron density of S. Therefore, we speculate that there is an interaction between IL and Pd species mainly through N and S. The charge transfer between IL and Pd species will be further confirmed from the following DFT calculations.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 53%
“…3(d)), peaks at 168.3 and 169.7 eV for fresh IL/Al 2 O 3 are corresponding to S 2p 3/2 and S 2p 1/2 of -SO 4 , respectively. 64,65 The binding energy in Pd-x%IL (x = 2, 4, 6) shifts to 168.8 and 170.2 eV, respectively, which also results in a decrease in electron density of S. Therefore, we speculate that there is an interaction between IL and Pd species mainly through N and S. The charge transfer between IL and Pd species will be further confirmed from the following DFT calculations.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 53%
“…In the first 200 min of weathering the sample was exposed to RH and CO 2 only. Correspondingly the growth of the following absorption bands can be observed at the following wavenumbers: 1342 s, 1221 w, and 1109 s. The 1221 and 1109 cm −1 bands have previously been observed 22 and correlated to the -C-O asymmetric stretch vibration and the asymmetric CO 3 2− stretch vibration of basic silver carbonate (AgOH.Ag 2 CO 3 ) surface species. The band at 1342 cm −1 not visible in conventional in situ IRRAS experiments (due to the occurrence of the bending vibration mode of the gas phase water) has been referred in literature to be the absorption frequency of the CO 2 symmetric stretching vibration in basic surface carbonates.…”
Section: B In Situ Time Resolved Pm-irras Measurements On a Silver Smentioning
confidence: 61%
“…The most important factors having an influence on atmospheric corrosion processes are the relative humidity (RH), temperature as well as gaseous pollutants and particulates present in the ambient atmosphere such as H 2 S, NO x , SO 2 , O 3 , etc. [1][2][3][4][5][6][7][8] . The complexity of atmospheric corrosion of different metals is due to the different physical and chemical surface reactions occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high electrical conductivity and low optical loses, Ag is currently the metal of choice for metal window electrode applications (Griffith et al, 2016), although it is recognized that its high cost may necessitate recycling if it is to be used in low cost applications such as organic photovoltaics (OPVs) (Krebs et al, 2014). Ag films are also sensitive to oxidation in ambient air, a process which is detrimental to their performance as electrodes in devices (Watanabe et al, 2007;Kim et al, 2009;Behrendt et al, 2015). Zhang et al (2014) have shown that alloying Ag with ∼10% aluminium by co-sputtering is a very effective approach for stabilizing optically thin Ag films without compromising the optical properties, although the sheet resistance of Al doped Ag electrodes is not as low as can be achieved with pure Ag.…”
Section: Introductionmentioning
confidence: 99%